Stress intensity factors for surface cracks in round bar under single and combined loadings - Ismail, Al Emran; Arifﬁn, A.K.; Abdullah, S.; Ghazali, M.J. (Springer International Publishing, 2012)
This paper numerically discusses stress in-tensity factor (SIF) calculations for surface cracks in round bars subjected to single and combined loadings. Different crack aspect ratios, a/b, ranging from 0.0 to 1.2 and the relative crack depth, a/D, in the range of 0.1 to 0.6 are considered. Since the torsion loading is non-symmetrical, the whole ﬁnite element model has been constructed, and the loadings have been remotely applied to the model. The equivalent SIF, F∗EQ is then used to combine the individual SIF from the bending or tension with torsion loadings. Then, it is compared with the combined SIF, F∗FE obtained numerically using the ﬁnite element analysis under similar loadings. It is found that the equivalent SIF method successfully predicts the combined SIF, F∗EQ for Mode I when compared with F∗FE . However, some discrepancies between the results, determined from the two different approaches, occur when FIII is involved. Meanwhile, it is also noted that the F∗FE is higher than the F∗EQ due to the difference in crack face interactions and de-formations.